Pengembangan Bahan Ajar IPA Terpadu untuk Meningkatkan Literasi IPA Siswa Kelas IV Kurikulum 2013 - Kustiarini - Rini (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2018)
International survey results TIMSS (2011) and PISA (2012) showed that Indonesian student science literacy is low when compared to other countries. Based on this, the research and development of integrated science teaching materials to improve literacy students Research and development aims to describe the characteristics, test validity, knowing legibility, as well as determine the effectiveness of learning by using teaching materials development results. Design test used is the pre-test and post-test control group were held in SDN Kleco 1 Surakarta. Valid teaching materials seen from the average expert assessment of the material that is 81.7%, is 90.8% of media experts, and practitioners that is 91.62%. Teaching materials easily understood by 14.36 t value greater than t table 1.83 with an average of 90.74 test results legibility is greater than 60. The teaching materials effectively improve students' literacy skills IPA seen from the increasing average postes Significant experimental class, with the results of the N-Gain of 0.53 was higher than the control class of 0.34. On average posttest experimental class is 83,03 and control class is 77,58. The average difference of 5.45. Based on the results of the study concluded that the teaching material meets the criteria of validity, readability and effectiveness. Material development is still limited, as well as scoring and leveling IPA literacy skills are not in accordance with the TIMSS standards, it is expected that there should be research related to these matters by subsequent researchers to obtain better results.